Influence of the Extension and Tax Service to Complience of Personal Tax in Indonesia (Study through Taxpayers in the Tax Court – Jakarta) - Iswanto, Yasir; Sumaryadi, I Nyoman; Achmad, Mansyur; Ruhana, Faria (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research will be limited/limited regarding specific matters relating to government policies (efforts) in increasing compliance, socializing and growing awareness of taxation, to people who are at least approaching "tax minded"; and will be focused on individual taxpayers concerning simplicity, easy to understand and easy to implement, and on the elements of its development (socialization, counseling, communication) in order to increase compliance and awareness of the taxation referred to, which is marked by an increase in the number of taxpayers reporting (intensification) and the number of taxpayers. Registered tax and its reporting figures as an extensification effort in the field of taxation; as well as looking at the aspect of fairness, in the sense that it has been conveyed evenly to all citizens, especially those who have met the subjective and objective requirements, are easy and can be understood and accepted by all. This research uses quantitative research methods; Khasan Effendy in his book "Integrating Quantitative and Qualitative Methods" (2010: 90), writes as follows: "Quantitative research is research that uses theory as a framework for the whole research". The results of the study show that the parties in the end are compliance and awareness to carry out their tax obligations, which means an increase in state revenues, because this involves the livelihood of many people, agencies, certain individuals, the government itself and the general public.